Novel Nuclear Signaling Pathway Mediates Activation of Fibroblast Growth Factor-2 Gene by Type 1 and Type 2 Angiotensin II Receptors - Peng, Hu (The American Society for Cell Biology, 2001)
In bovine adrenal medullary cells synergistically acting type 1 and type 2 angiotensin II (AII) receptors activate the fibroblast growth factor-2 (FGF-2) gene through a unique AII-responsive promoter element. Both the type 1 and type 2 AII receptors and the downstream cyclic adenosine 1′,3′-monophosphate- and protein kinase C-dependent signaling pathways activate the FGF-2 promoter through a novel signal-transducing mechanism. This mechanism, which we have named integrative nuclear FGF receptor-1 signaling, involves the nuclear translocation of FGF receptor-1 and its subsequent transactivation of the AII-responsive element in the FGF-2 promoter.